Managing Business Processes in Banking - A. A. Tarasov (Управленческие науки, 2017)
Introduction, Purpose. The article describes the management of business processes in the activities of banks in primary capital markets. This type of banking business is an important one in the financial market, since the role of modern banks includes the execution of profitable transactions to bring investors into the securities of corporations during the placement process (equity, Eurobonds, and consulting services) on the international capital markets. For Russian borrows the full range of such services is offered by the largest Russian and leading international investment banks. Methods. This study is focused on the development of the key managerial business-processes: strategy and forecasting, benchmarking and SWOT-analysis, KPIs and budgeting, operational and financial managerial accounting. The achieved results include the samples of banking business-processes management instruments based on the methods of competitive analysis, analytical forecasting, and financial management. Results. The applied methods allow the optimal planning and monitoring the results of the capital markets business, including quantitative assessments of following the strategy and achieving the desired goals. Discussion. The obtained results can be used to analyze the functional responsibilities of the Department to work in capital markets (preparation of commercial proposal, obtaining internal approval in the Bank, stage of the syndication, preparation of documentation, closing of the transaction), as well as interaction with other departments of the Bank business development (including risks, Finance, strategy).